The mediating effect of attitudes towards statistics and technology in university students - Silva, Osvaldo Dias Lopes da (2023)
ABSTRACT: University students, especially those who study Social Sciences and Humanities, tend to express their fear at the beginning of classes in curricular units in Statistics, foreseeing possible difficulties in their learning. To evaluate and monitor the performance of students in Statistics course units, it is of utmost relevance that teachers and researchers consider some non-cognitive factors related to the students, such as the anxiety revealed in evaluation periods and the attitudes that students have in relation to Statistics and the use of Technology in these curricular units. In a post-pandemic period, the objective of this study is to investigate the interrelationships between some constructs and the potential mediating effect of attitudes towards Statistics and Technology on the relationship between anxiety and students' performance in these curricular units. The data was obtained through the questionnaire containing variables of sample characterization, seven items concerned the Anxiety dimension of the Depression Anxiety Stress Scale (Lovibond & Lovibond, 1995), 28 items of the Students’ Attitudes toward Statistics and Technology Scale (Anastasiadou, 2011) and, also, the variable referring to the performance of students in Statistics, operationalized based on the classifications obtained within the scope of the respective curricular unit in the area of Statistics. Higher scores in the Anxiety dimension correspond to higher levels of student anxiety. Students’ Attitudes Toward Statistics and Technology Scale allows identifying the positive/negative attitudes associated with lived experiences in the context of learning Statistics with the use of Technology. ....[...].... In terms of data analysis procedures, a descriptive analysis, and the evaluation of the internal consistency of the items of the instruments used were carried out, based on Cronbach's Alpha coefficient. To test the mediation hypothesis, the Process macro (Hayes, 2021) was used, with the decision on the significance of the indirect effect based on the bootstrap estimation. The potential mediating effect of attitudes towards Statistics and Technology on the relationship between anxiety and performance was verified, that is, the indirect effect was statistically significant. It was also found that: anxiety was negatively associated with attitudes towards Statistics and Technology; attitudes towards Statistics and Technology were positively associated with performance; and anxiety was negatively associated with performance (significant direct effects).